Evaluation of the Tribal Strategies Against Violence (TSAV) Initiative in Four Tribal Sites in the United States, 1995-1999 - Nichols, V. Richard ([Verlag nicht ermittelbar], 2005)
This study evaluated the Tribal Strategies Against Violence (TSAV) Initiative. The TSAV was a federal-tribal partnership, lasting from 1995 to 1999, designed to develop comprehensive strategies in tribal communities to reduce crime, violence, and substance abuse. This study involved four of the seven TSAV sites: the Chickasaw Nation in Oklahoma, Fort Peck Assiniboine and Sioux Tribes in Montana, the Grand Traverse Band of Ottawa and Chippewa Indians in Michigan, and the Turtle Mountain Band of Chippewa Indians in North Dakota. A survey of TSAV stakeholders at the four sites was conducted in the summer and fall of 1999. The objectives of the survey were to gauge TSAV stakeholders' perceptions about the following: (1) the serious crime, violence, and quality of life issues in each community and the extent to which the local TSAV initiative had addressed those issues, (2) the intent and ultimate outcomes of the TSAV program, (3) obstacles to successful implementation of TSAV activities, and (4) decision-making processes used in planning and implementing TSAV locally. Offense data were also gathered at the Fort Peck site for 1995 to 1998 and at the Grand Traverse Band site for 1997 to 1999.